Anorexia of the Main The Character in Movie Entitled “To The Bone” - Jimmi Jimmi; Bonita Narulita; Juniato Sidaruk (Musamus Journal of Language and Literature, 2021)
The aim of this research is to figure out about the symptoms and the treatment of the Anorexia in the movie entitled “To the Bone”. The researcher chooses “To the Bone” movie because the movie provides Anorexia disorder that occurred in the main character, Ellen, as the main analysis of this theme movie. The object of this research is about movie entitled “To the Bone” due to this movie provides shown Anorexia appeared in the main character. The researcher applies descriptive qualitative method to analyze the “To the Bone” movie. The data are analyzed using the anorexia theory from Pamela I. Swain. The data as the results of this analysis are (1) There are six symptoms of Anorexia in the main character are always wear baggy clothes, weight less than 85 percent normal, downy hair grows in arms, extremely low-calorie diet, compulsive exercise, refuse for not eating; (2) The treatments of anorexia for the main character are refeeding and psychotherapy counseling that consists of family counseling, group counselling, and personal counselling.